1999
DOI: 10.1897/1551-5028(1999)018<0318:eosbbt>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sediment Bioturbation by the Estuarine Amphipod Corophium Volutator on Fluoranthene Resuspension and Transfer Into the Mussel (Mytilus Edulis)

Abstract: Abstract-To better understand the effects of bioturbation on partitioning and availability of sediment-bound contaminants to infaunal amphipods and mussels, experiments were carried out with fluoranthene-spiked sediment. Treatments included different densities of the estuarine amphipod, Corophium volutator. Total suspended solids (TSS), particulate organic carbon/particulate organic matter (POC/POM) in overlying water, fluoranthene concentrations in sediment, pore water, overlying water, amphipods, and mussels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(53 citation statements)
references
References 33 publications
1
51
0
1
Order By: Relevance
“…For example, mayfly (Hexagenia rigida) and Asian clam (Corbicula fluminea) had less uptake of Cd and Zn in bioturbated systems than in unbioturbated systems [163]. However, bioturbation by amphipods significantly increased Johnston TSS concentration in the overlying water and, consequently, the total aqueous concentration of sediment-bound fluoranthene, which was subsequently accumulated by filter-feeding mussels [164]. The importance of resuspension events on contaminant release will be a function of several factors.…”
Section: Suspended Solids and Resuspended Sedimentsmentioning
confidence: 99%
“…For example, mayfly (Hexagenia rigida) and Asian clam (Corbicula fluminea) had less uptake of Cd and Zn in bioturbated systems than in unbioturbated systems [163]. However, bioturbation by amphipods significantly increased Johnston TSS concentration in the overlying water and, consequently, the total aqueous concentration of sediment-bound fluoranthene, which was subsequently accumulated by filter-feeding mussels [164]. The importance of resuspension events on contaminant release will be a function of several factors.…”
Section: Suspended Solids and Resuspended Sedimentsmentioning
confidence: 99%
“…it increases exchange surface with water column and modifies sediment physical properties as porosity, permeability, compaction and stability (Rhoads, 1974;McCall and Fisher, 1980;Meadow and Tait, 1989;Sandness et al, 2000;DeDekere et al, 2001;Ciutat et al, 2006;Rasmussen et al, 1998). As they often actively irrigate their galleries by flushing, they enhance the exchange of solutes and particles between the sedimentary compartment and the free overlying water (Ciarelli et al, 1999, Meysman et al, 2006.…”
Section: Interactions Between Benthic Organisms and The Sedimentmentioning
confidence: 99%
“…dredging and trawling). Bioturbation refers to the disturbance caused by the activities of sediment-dwelling macroinvertebrates, and includes activities such as burrowing, feeding, defecating, and tube-building (Ciarelli et al, 1999). An example of the importance of bioturbation activities is evident in a study by Hedman et al (2009), where researchers found greater amounts of polychlorinated biphenyl (PCBs) were emitted to water by bioturbation of the amphipod Monoporeia affinis than that by physical resuspension.…”
Section: Introductionmentioning
confidence: 99%
“…If more HOCs are released into the water phase, bioturbation may substantially enhance HOC bioavailability (Thibodeaux and Bierman, 2003). Although previous studies (Ciarelli et al, 1999;Friedman et al, 2009;Schuler et al, 2002) have shown that bioturbation significantly changed HOC distribution between sediment and water, limited studies have been conducted to evaluate the effects of bioturbation by freshwater oligochaetes on bioavailability and toxicity of sediment-associated HOCs to other benthic and epi-benthic organisms.…”
Section: Introductionmentioning
confidence: 99%